Eco‐energetic consequences of evolutionary shifts in body size. (15th November 2017) - Malerba, Martino E.; White, Craig R.; Marshall, Dustin J.
Abstract: Size imposes physiological and ecological constraints upon all organisms. Theory abounds on how energy flux covaries with body size, yet causal links are often elusive. As a more direct way to assess the role of size, we used artificial selection to evolve the phytoplankton species Dunaliella tertiolecta towards smaller and larger body sizes. Within 100 generations ( c . 1 year), we generated a fourfold difference in cell volume among selected lineages. Large‐selected populations produced four times the energy than small‐selected populations of equivalent total biovolume, but at the cost of much higher volume‐specific respiration. These differences in energy utilisation between large (more productive) and small (more energy‐efficient) individuals were used to successfully predict ecological performance ( r and K ) across novel resource regimes. We show that body size determines the performance of a species by mediating its net energy flux, with worrying implications for current trends in size reduction and for global carbon cycles.